Academic Information System in Nurul Falah Islamic Foundation in Garut District Web-Based - Fallah, Herlina Sumil (Jurnal Manajemen Informatika Medicom (JMI), 2024)
Academic, namely activities carried out within the world of education related to the teaching and learning process. The academic information system at the Nurul Falah Islamic Education Foundation is considered ineffective where recording student data, teacher data, subject data, student class data, scheduling and assessment are still recorded in books so they are easily damaged or lost and making reports takes a long time. This study aims to determine the current system, make system design, analyze and test the system and to implement academic information systems. The method for designing the system used by the author in this study is the waterfall method where the data collection techniques used include observation, interviews and literature study. The development method uses a structured method with several tools and processing techniques such as flowmaps, context diagrams, and data flow diagrams. The programming language used in designing and implementing academic information systems is PHP and the database used is MySQL.